ANALYSIS OF DIFFERENCES IN TRIGLYCERIDE LEVELS BETWEEN TOBACCO SMOKERS AND ELECTRIC SMOKERS IN STUDENTS (ORMAWA) OF MUHAMMADIYAH UNIVERSITY OF SIDOARJO - Mukarromah, Rizka Aisya; Hanum, Galuh Ratmana; Rohmah, Jamilatur; Rini , Chylen Setiyo (Antis-Publisher, 2025)
Objective: The aim of this study was to analyze the differences in triglyceride levels between tobacco smokers and e-smokers among students (ORMAWA) at Muhammadiyah University of Sidoarjo. Method: The design used in this research was quantitative with experimental tests using a cross-sectional approach. The population of this study included all male Ormawa students at Muhammadiyah University of Sidoarjo with the habit of smoking tobacco and e-smoking, totaling 532 students, with a sample size of 16 tobacco smokers and 16 e-smokers. The sampling method used is Quota non-probability sampling. This research was conducted at the hospital. Bhayangkara Pusdik Sabhara Porong in August 2024. The samples in the study were read using a DIALAB brand autolyzer with the colorimetric enzymatic method (GPO-PAP). Data from examination of triglyceride levels were analyzed statistically using the t-Independent test. Results: The results showed that there was no significant difference, namely 0.055 (p<0.05) between tobacco smokers and electronic smokers among students (Ormawa) at Muhammadiyah University of Sidoarjo. Novelty: This study provides comparative data on triglyceride levels between tobacco and electronic cigarette users within a specific university student organization population, which has not been widely studied in the Indonesian context.